Dissecting the chromosome-level genome of the Asian Clam (Corbicula fluminea) - Tongqing Zhang; Jiawen Yin; Shengkai Tang; Daming Li; Xiankun Gu; Shengyu Zhang; Weiguo Suo; Xiaowei Liu; Yanshan Liu; Qicheng Jiang; Muzi Zhao; Yue Yin; et al. (Scientific Reports, 2021)
Abstract The Asian Clam (Corbicula fluminea) is a valuable commercial and medicinal bivalve, which is widely distributed in East and Southeast Asia. As a natural nutrient source, the clam is rich in protein, amino acids, and microelements. The genome of C. fluminea has not yet been characterized; therefore, genome-assisted breeding and improvements cannot yet be implemented. In this work, we present a de novo chromosome-scale genome assembly of C. fluminea using PacBio and Hi-C sequencing technologies. The assembled genome comprised 4728 contigs, with a contig N50 of 521.06 Kb, and 1,215 scaffolds with a scaffold N50 of 70.62 Mb. More than 1.51 Gb (99.17%) of genomic sequences were anchored to 18 chromosomes, of which 1.40 Gb (92.81%) of genomic sequences were ordered and oriented. The genome contains 38,841 coding genes, 32,591 (83.91%) of which were annotated in at least one functional database. Compared with related species, C. fluminea had 851 expanded gene families and 191 contracted gene families. The phylogenetic tree showed that C. fluminea diverged from Ruditapes philippinarum, ~ 228.89 million years ago (Mya), and the genomes of C. fluminea and R. philippinarum shared 244 syntenic blocks. Additionally, we identified 2 MITF members and 99 NLRP members in C. fluminea genome. The high-quality and chromosomal Asian Clam genome will be a valuable resource for a range of development and breeding studies of C. fluminea in future research.